Bahasa Inggris - Rukin Rukin (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2026)
Rural development planning in Indonesia has increasingly incorporated climate adaptation frameworks; however, significant gaps remain between planning documents and implementation practices. This study aims to analyze the misalignments between village development plans, land use priorities, and climate risk assessments in selected rural areas. Using a qualitative case study approach, data were collected through document analysis, in-depth interviews with village officials, and focus group discussions with community members. The findings reveal persistent contradictions between short-term economic objectives such as palm oil expansion and infrastructure development and long-term ecological sustainability. Climate risk maps and spatial plans were found to be inconsistently applied or ignored altogether at the village level, often due to fragmented data systems, top-down policy directives, and limited community engagement. Moreover, institutional silos and donor-driven agendas further exacerbate the incoherence of policy implementation, undermining resilience-building efforts. Informants highlighted that alternative livelihoods such as agroecology and ecotourism, while environmentally sound, lacked institutional support and integration into formal planning mechanisms. This study concludes that policy incoherence stems from both structural and procedural limitations, resulting in feedback loops that reinforce rural vulnerability. It recommends a systemic shift toward harmonized, cross-sectoral governance frameworks that promote ecological justice, empower local communities, and operationalize adaptive planning. The research offers practical insights for policymakers, development practitioners, and scholars concerned with sustainable rural transformation in the face of socio-ecological disruption.